2020
DOI: 10.1111/padm.12665
|View full text |Cite
|
Sign up to set email alerts
|

Developing a short scale to assess public leadership

Abstract: Tummers and Knies (2016) have recently introduced a 21‐item scale for the measurement of public leadership to the burgeoning field of leadership research in public administration. However, due to restrictions in survey length and response time, scholars often face practical difficulties when adopting measurement scales of such length. In many subfields of public administration, this results in a proliferation of ad hoc measures of unknown validity, which impedes scholarly progress. The goal of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…These were, "thinking about your most recent contact with police answer, the police were efficient," "the police did their job and took appropriate action," "the police were prompt," and "the police kept me informed and followed up." The accountability of the police officials was measured with 3-items adapted from Vogel, Reuber, and Vogel (2020). The sample items included police officials/institution "explain their actions to citizens," "inform citizens about the way of their working," and "strives to ensure that they openly and honestly share the actions of the individuals and institution with citizens.…”
Section: Study Measuresmentioning
confidence: 99%
“…These were, "thinking about your most recent contact with police answer, the police were efficient," "the police did their job and took appropriate action," "the police were prompt," and "the police kept me informed and followed up." The accountability of the police officials was measured with 3-items adapted from Vogel, Reuber, and Vogel (2020). The sample items included police officials/institution "explain their actions to citizens," "inform citizens about the way of their working," and "strives to ensure that they openly and honestly share the actions of the individuals and institution with citizens.…”
Section: Study Measuresmentioning
confidence: 99%
“…In this context, managing the COVID-19 crisis highlights the critical need for effective public leadership, a form of collective leadership in which public bodies and agencies collaborate to generate public value for the common good (Brookes, 2011; Getha-Taylor et al , 2011). While some scholars focus on a narrow definition of public leaders as administrative officials that manage government and non-profit agencies (Van Wart, 2013; Vogel et al , 2020), a broader view also includes elected political leaders (Ospina, 2017). Among the many competing demands public leaders face, two that are commonly highlighted in the literature are the tension between political responsiveness and administrative responsibility as well as the changing nature of leadership roles amidst increasing cross-sectoral collaboration (Kirlin, 1996; Jung et al , 2008; Vogel and Masal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on leadership in the public sector has focused on different types of leadership, such as transformational, transactional, and servant leadership, which have been measured through surveys administered to leaders and their subordinates (Jacobsen and Andersen 2015;Oberfield 2014;Schwarz et al 2016). Recent studies have also suggested specific aspects of public leadership and developed survey instruments to obtain information about these leadership behaviors (Tummers and Knies 2016;Vogel, Reuber, and Vogel 2020). The aim of our study is not so much to focus on specific aspects of leadership but rather to investigate how self-reported measures of leadership, in general, can be affected by nonresponse bias.…”
Section: Introductionmentioning
confidence: 99%